Izoglose v prekmurskem narečju – regionalna geolingvistika - Horvat, Mojca (Slavia Centralis, 2020)
Isoglosses in the Prekmurje Dialect – Regional Geolinguistics The paper contributes to Slovenian regional geolinguistics, which deals with linguistic phenomena on the regional level. To date regional areal linguistics has been applied in two of the Slovenian dialect groups, the Littoral and the Carinthian dialect groups. According to Mario Alinei, this type of linguistic atlas is defined as second generation atlases (while first generation atlases are national atlases, and the third atlases of language groups – e. g., OLA, and, finally, fourth generation atlases are those of nonrelated languages (continental atlas) – ALE. The importance of regional lingustic atlases will be presented by the case study based on linguistic maps representing Prekmurje dialect linguistic features. Considering the newest phonetical features, this dialect could be divided into three subdialects (dolinsko, ravensko, goričko). In the present paper, selected linguistic features will be presented on the regional linguistic maps with the method of the geolinguistics, as they are transcribed in the data base for Slovenian Linguistic Atlas.